James McGill: A Critical Biographical Study - Macsporran, Maysie Steel (Université McGill, 1930)
Keywords: McGill, James; Université McGill

Sir William C. Macdonald; Benefactor to Education - Epstein, Murray Hart (Université McGill, 1969)
Keywords: Macdonald, William C.; Université McGill

James McGill of Montreal - Frost, Stanley Brice (McGill-Queen's University Press, 1995)
Keywords: McGill, James; Université McGill

Les étapes de la science économique au Québec: démarrage, construction et maturité - Fortin, Pierre (L'Actualité économique, 2000)
Keywords: Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal

Wine and Food / Cuisine et vins - M. Romoff, Harvey (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Alcool; Alimentation; Clubs; Restaurant; University Club; Université McGill

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald, William C.; Philanthropie; Tabac; Université McGill

John Wilson McConnell. Homme d'affaires, éditeur de journal, humaniste et philanthrope canadien / John Wilson McConnell: Canadian businessman, newspaper publisher, humanitarian, and philanthropist - Nieuwendyk, Dick (Héritage Dorval, 2016)
Keywords: Hommes d'affaires; McConnell, John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

L’émeute des tramways de Montréal (1955) et la mauvaise conduite des étudiants: un cas d’appropriation de l’espace urbain - Poitras, Daniel (Urban History Review / Revue d'histoire urbaine, 2018)
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Délinquance; Tramways; Transport en commun; Université McGill; Université de Montréal; Émeutes; Étudiants

J.W. McConnell: Financier, Philanthropist, Patriot - Fong, William Jesse (McGill-Queen's University Press, 2008)
Keywords: Clubs; Hommes d'affaires; McConnell, John Wilson; Montreal Star; Philanthropie; Sucre; Université McGill

Science et technologie à Montréal: la longue naissance d'une ville du savoir - Trépanier, Michel (Histoire de Montréal et de sa région, 2012)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

Science and Technology: The Coming of Age of a City of Knowledge - Trépanier, Michel (Montreal: The History of A North American City, 2018)
Keywords: Association canadienne-française pour l'avancement des sciences (ACFAS); Avionnerie; Botanique; Chimie; Ingénieurs; Jardin botanique; Marie-Victorin, Frère; Physique; Université Concordia; Université McGill; Université de Montréal; Université du Québec à Montréal; École polytechnique

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Université McGill, Département de géographie, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

The Layered City: A Revolution in Housing in Mid-Nineteenth-Century Montreal - Hanna, David B. (Université McGill, Département de géographie, 1986)
Keywords: Logement

A City of Tenants: Home-Ownership and Social Class in Montreal, 1847-1881/Une ville de locataires : propriété résidentielle et classes sociales à Montréal de 1847 à 1881 - Hertzog, Stephen (Université McGill, Departement de géographie, 1985)
Keywords: Locataires; Logement

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

Private Rehabilitation in a Low Rent Area: Landlord-Tenant Relations and other Non-Market Factors - Duff, Huntly Douglas (Université McGill, 1973)
Keywords: Locataires; Logement; Portugais

Entre globalisation et réalités locales: centres commerciaux et formes urbaines à Los Angeles, Montréal et Paris / Between Globalization and Local Realities: Shopping Centers and Urban Forms in Los Angeles, Montreal and Paris - Moretti, GianPiero (Université McGill, 2004)
Keywords: Centres commerciaux

Enforcing the Right to Healthy Housing: Recourse for Montreal Tenants Facing Health and Safety Problems at Home - Auchinleck, Jennifer (Université McGill, 2011)
Keywords: Locataires; Logement

Design Considerations in Urban Low-Income Housing Redevelopment with Special Reference to Montreal - Chan, David Wai (Université McGill, 1970)
Keywords: Logement

Accessibility: A Performance Measure for Land-Use and Transportation Planning in the Montréal Metropolitan Region - Cerdá, Assumpta (Université McGill, 2009)
Keywords: Navettage

Falling Up and Staying High: Commute Transit Mode Share Trends in Montreal Age Groups and Birth Cohorts - Grimsrud, Michael (Université McGill, 2013)
Keywords: Transport en commun

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

The Economics of Assembly and Transportation of Fluid Milk in the Montreal Area - Shipley, William Charlton (Université McGill, 1950)
Keywords: Lait

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

Using E-Government to Strengthen Montreal's Chinese Ethnic Economy - Han, Yang (Université McGill, 2006)
Keywords: Chinois; Commerce de détail; Internet

The Development of Complex Commercial Projects in Central Areas with Special Reference to Montreal - Ng, Spencer Che Lou (Université McGill, 1965)
Keywords: Gratte-ciel

Inter-Urban Industrial Linkages in Montreal's Hinterland - Murricane, Kenneth (Université McGill, 1975)

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

La relation entre l'évolution du salaire réel et de l'emploi: Montréal, 1963-1982 - Dagenais, Vincent (Université McGill, 1990)

Destination, Housing and Quality of Life in the Migrant Experience from Larino (Molise, Italy) to Milano and Montreal - Fainella, John G. (Université McGill, 1996)
Keywords: Italiens; Logement

For the Benefit of the Master: the Montreal Needle Trades During the Transition, 1820-1842 - Poutanen, Mary Anne (Université McGill, 1986)
Keywords: Apprentissage; Confection; Femmes

Édouard-Raymond Fabre, bourgeois patriote du Bas-Canada, 1799-1854 - Roy, Jean-Louis (Université McGill, 1972)
Keywords: Fabre, Édouard-Raymond; Librairie; Maires; Rébellions

An Index to Retail Market Prices in Montreal 1843-1867 - Horovitz, William Bela (Université McGill, 1967)
Keywords: Prix

The Application of Steam Navigation to the St. Lawrence 1809-1840 - Wilson, George H. (Université McGill, 1961)
Keywords: Navigation; Énergie hydraulique

The Montreal Ship Channel, 1805-1865 - Corley, Nora (Université McGill, 1961)
Keywords: Navigation

Internal Dynamics and the International Cycle: Questions of the Transition in Montreal, 1821-1828 - Sweeny, Robert (Université McGill, 1985)
Keywords: Artisans; Banque de Montréal; Banques; Bourgeoisie; Hommes d'affaires; Marchands

Working for Family, Nation and God: Paternalism and the Dupuis Frères Department Store, Montreal, 1926-1952 - Matthews, Mary Catherine (Université McGill, 1997)
Keywords: Commerce de détail; Dupuis Frères; Magasins; Travail

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Le rôle des déterminismes sociaux dans le développement des forces productives de l'industrie textile du Canada, 1870 à 1910 - Ferland, Jacques (Université McGill, 1982)
Keywords: Textile

Spatial Aspects of Real Estate Transactions an Exploratory Study of the Island of Montreal: 1947-1967 - De Jong, Nicolas J. (Université McGill, 1971)

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Cyclist Injury Risk and Pollution Exposure at Urban Signalized Intersections - Strauss, Jillian (Université McGill, 2012)
Keywords: Cyclisme; Pollution

La motorisation ou "La rançon du progrès". Tramways, véhicules-moteurs et circulation (Montréal, 1900-1930) - Veilleux, Denis (Université McGill, 1998)
Keywords: Automobile; Tramways; Transport en commun

Les aubergistes et les cabaretiers à Montréal en 1700 - Poliquin, Marie-Claude (Université McGill, 1996)
Keywords: Auberges

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

The Movement for Public Housing in Montreal, 1930-1958 - Ruddick, Susan M. (Université McGill, 1979)
Keywords: Logement

A Study of the Point St. Charles Shops of the Grand Trunk Railway in Montreal, 1880-1917 - Hoskins, Ralph F. H. (Université McGill, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

Spatial Patterns of Selected Retail Activities, Montreal 1950-1970 - Bouchard, Diana C. (Université McGill, 1972)
Keywords: Commerce de détail

The Port of Montreal - Tombs, Laurence Chalmers (Université McGill, 1926)
Keywords: Port

The Impact of the St. Lawrence Seaway on the Port of Montreal - Slack, Brian (Université McGill, 1963)
Keywords: Navigation; Port; Voie maritime

Housing in the Suburban Region of Montreal, 1951-1961 - Dernoi, Louis Anthony (Université McGill, 1964)
Keywords: Banlieue; Logement

Montreal, a City Built by Small Builders, 1867-1880 - Hanna, David B. (Université McGill, 1987)
Keywords: Logement

Spatial Aspects of Real Estate Transactions: An Exploratory Study of the Island of Montreal, 1947-1967 - Dejong, Nicolas J. (Université McGill, 1971)

The Sun Life Insurance Company of Montreal, 1872-1900 - Pollack, Gladys (Université McGill, 1980)
Keywords: Assurance; Sun Life Assurance

History and Organisation of the Montreal Stock Exchange - Johnson, J. S. (Université McGill, 1934)
Keywords: Bourse

The Montreal Garment Industry, 1871-1901 - Payette-Daoust, Michelle (Université McGill, 1986)
Keywords: Confection

Industrial Location in the City of St. Laurent - Isenberg, Seymour (Université McGill, 1967)
Keywords: Saint-Laurent (ville)

Montreal Regional Industrial Pattern as Compared to that of Toronto - Fisher, David (Université McGill, 1940)

Montreal Chinese Property Ownership and Occupational Change, 1881-1981 - Aiken, Rebecca Bruff (Université McGill, 1985)
Keywords: Chinois; Travail

Social Mobility in the Home-Building Industry in Montreal, 1951-1961 - Rawin, Solomon John (Université McGill, 1962)
Keywords: Logement

Farm Leases and Agriculture on the Island of Montreal, 1780-1820 - Waywell, Jennifer L. (Université McGill, 1989)
Keywords: Baux à ferme; Notaires

A Stake in the System: Domestic Property Ownership and Social Class in Montreal, 1847-1881 - Hertzog, Stephen (Université McGill, 1984)
Keywords: Logement

La Banque du Peuple, 1835-1871, and its Failure, 1895 - Greenfield, Robert S. (Université McGill, 1968)
Keywords: Banque du Peuple; Banques

Development of High-Rise Habitation in Central Urban Areas with Special Reference to Montreal - Raina, S. K. (Université McGill, 1974)
Keywords: Logement

The Construction Industry in Montreal with Special Reference to Seasonal Unemployment - Berman, Alfred (Université McGill, 1931)
Keywords: Chômage

Changes in the Intra-Urban Land-Value Surface: The Impact of Transportation, Land-Use and Socio-Economic Factors in Central Montreal - Foggin, Peter M. (Université McGill, 1970)

The Lachine Canal - Cureton, Edward A. (Université McGill, 1957)
Keywords: Lachine (canal); Navigation

The Construction of the First Lachine Canal, 1815-1826 - Tulchinsky, Gerald (Université McGill, 1960)
Keywords: Lachine (canal); Navigation

Providing a Home and then Some: A study of Montreal's Homeownership Programme - Pinches, Brendan James (Université McGill, 2010)
Keywords: Logement

Climate Change Adaptation and Mitigation through Urban Agriculture: A Montreal Case Study - Lebedeva, Julia (Université McGill, 2008)
Keywords: Climat

Loft Conversions in a Local Context: The Case of Inner City Montreal - Podmore, Julie (Université McGill, 1994)
Keywords: Logement

Housing without Families: The Housing Situation of Non-Family Households in Montreal - Lavigne, Jean-François (Université McGill, 1988)
Keywords: Logement

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

Residential Rehabilitation - with Special Reference to Montreal - Santiago, Arturo M. (Université McGill, 1975)
Keywords: Logement

Mutual Aid Networks in Two Feminist Housing Co-Operatives in Montreal - Yasmeen, Gisèle (Université McGill, 1991)
Keywords: Féminisme; Logement

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Landlord Subsidization by Tenants in East End Montreal - Kovitz, Marcia Mitzi Ruth (Université McGill, 1975)
Keywords: Locataires; Logement

Uncompleted Condominiums: A Strategy for Cost Reduction in Montreal Housing - Kowalska, Danuta (Université McGill, 1991)
Keywords: Logement

The Ownership of Old Rental Housing in an Appreciating Central Montreal Neighborhood - Roberts, Marilyn Manzer (Université McGill, 1972)
Keywords: Logement

Space about Multiple Dwellings with Special Reference to Montreal - Steber, George Jr. (Université McGill, 1963)
Keywords: Logement

The Restructuring of the Montreal Tourism Industry: A Sectoral Analysis - Pohlmann, Corinne (Université McGill, 1994)
Keywords: Tourisme

The Social Organization of Residential Real Estate - House, John Douglas (Université McGill, 1972)

Rethinking Trench Expressways: Urban Design Strategies with Applications to Montreal's Décarie Autoroute - Richer, Nadia (Université McGill, 2010)
Keywords: Autoroutes

Montreal Electric Streetcar Suburbanization: A Study of a Canadian City’s Morphological Transformation Before World War 1 - Karczmar, Christine Elizabeth (Université McGill, 2013)
Keywords: Banlieue; Tramways

L'article 29 de la convention de Montréal: clef de voûte de la responsabilité du transporteur aérien international - Chassot, Laurent (Université McGill, 2009)
Keywords: Aéroport

Vehicle-Pedestrian Accidents at Signalized Intersections in Montréal - Fernandes, David (Université McGill, 2013)
Keywords: Rues

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)

The Changing Character of Streets in Central Areas with Special Reference to Sherbrooke Street as a Principal Street in City of Montreal-Canada - Rege, Ratan M. (Université McGill, 1966)
Keywords: Rues; Sherbrooke (rue)

Insuring against every man : an economic and social history of the Guarantee Company of North America, 1871-1919 - Doyon, Charles (Université McGill, 1980)
Keywords: Fiducie; Guarantee Trust Company

Ethnicity and Housing Adaptation: the Italians in Montreal - Fainella, John G. (Université McGill, 1986)
Keywords: Italiens; Logement

A Survey of Industrial Estates with Special Reference to Montreal - Grasser, Otto (Université McGill, 1964)

Can Transit and Spatial Planning Synergy Work at the Regional Scale? Understanding Metropolitan Transit-Oriented Development Planning and its Challenges in the Canadian City-Regions of Toronto, Montreal and Vancouver - Hamzah, Muhammad Zulkarnain (Université McGill, 2013)
Keywords: Transport en commun

Shaping Time in the City: A Cultural History of Concrete Modernity in Montreal, 1903-2015 - Charles, Julia Morgan (Université McGill, 2015)
Keywords: Autoroutes; Béton; Port; Stade olympique

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

A Voice of English-Montreal. The First Twenty Years of Véhicule Press, 1973-1993 - Hemond, Amy (Université McGill, 2019)
Keywords: Imprimerie; Poésie; Édition

Settling an 18th Century Faubourg: Property and Family in the Saint-Laurent Suburb, 1735-1810 - Stewart, Alan M. (Université McGill, 1988)
Keywords: Famille; Faubourgs; Quartiers; Saint-Laurent (quartier)

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)